Design and validation of a custom-made system to measure transepithelial electrical impedance in human corneas preserved in active storage machine - Marielle Mentek; Benjamin Peyret; Siwar Zouari; Sébastien Urbaniak; Jean-Marie Papillon; Emmanuel Crouzet; Chantal Perrache; Sophie Hodin; Xavier Delavenne; Zhiguo He; Philippe Gain; Gilles Thuret (Elsevier, 2024)
Corneal epithelial barrier represents one of the major limitations to ocular drug delivery and can be explored non-invasively through the evaluation of its electrical properties. Human corneas stored in active storage machine (ASM) could represent an interesting physiological model to explore transcorneal drug penetration. We designed a new system adapted to human corneas preserved in ASM to explore corneal epithelial barrier function ex-vivo. A bipolar set-up including Ag/AgCl electrodes adaptors to fit the corneal ASM and a dedicated software was designed and tested on freshly excised porcine corneas (n = 59) and human corneas stored 14 days in ASM (n = 6). Porcine corneas presented significant and proportional decrease in corneal impedance in response to increasing-size epithelial ulcerations and acute exposure to benzalkonium chloride (BAC) 0.01 and 0.05%. Human corneas stored 14 days in ASM presented a significant increase in corneal impedance associated with the restoration of a multi-layer epithelium and an enhanced expression of tight junctions markers zonula occludens 1, claudin 1 and occludin. These results support the relevance of the developed approach to pursue the exploration and development of human corneas stored in ASM as a physiological pharmacological model.